The Effect of Visual Concurrent (Mirror) Feedback on Static Balance in 7-13 Years Old Girls - Elham Lashani; Shahzad Tahmasebi (University of Tehran, 2015)
the purpose of this research was the effect of visual concurrent feedback on balance ability in 7-13 years old girls. Hence, for this purpose, thirty-four girls student (ranging 7-12 years old) were participated in this study. The students were divided to three group randomly, control, closed eyes and mirror visual concurrent feedback groups, after stork balance test pre-test. Then, groups under interventions completed related trainings. In the present study used paired t-test for comparison of intra-group and one- way ANOVA for inter group (p≤0.05). The result of ANOVA showed that there was no significant difference between pre-test (p≥0/05). But, there was significant improvement in mirror group compared to control group (p=0.001) and closed eyes group (p=0.001). In addition to, the result of paired t-test indicated that only the mirror group has significant progress (p=0.007) in balance and the other groups have significant decrements. Therefore, concurrent feedback in children by use of a mirror to show them self can be improve their balance ability